Synthesis and Spectroscopic Studies of Mixed Ligand Complexes of Pt(II) and Pd(II) with Ethyl-α-Isonitrosoacetoacetate and Dienes - Taksande, Anita Krishankant; Raut, Ravishankar D.; Choudhary, Mahendra D. (Orbital: The Electronic Journal of Chemistry, 2015)
The mixed ligand complexes of the kind [M(L1) (L2)] where M= Pt(II), Pd(II).L1 = primary ligand ethyl-α-isonitrosoacetoacetate derived from reaction between ethyl acetoacetate, acetic acid and sodium nitrite and L2=secondary ligand para-phenyldiamine (PPD) are synthesized. All the prepared complexes were identified and confirmed by elemental analysis, molar conductance measurements, and infrared electronic absorption. Their complexes has been made based on elemental analysis, molar conductivity, UV-Vis, FT-IR and 1HNMR spectroscopy and magnetic moment measurements as well as thermal analysis (TGA and DTA). The elemental analysis information recommends that the stoichiometry of the complexes to be 1:2:1. The molar conductance measurements of the complexes indicate their non-electrolytic nature. The infrared spectral information showed the coordination sites of the free ligand with the central metal particle. The electronic absorption spectral information disclosed the existence of an octahedral geometry for Pt(II) and Pd(II) complexes. DOI: http://dx.doi.org/10.17807/orbital.v7i4.633